Language Use and Language Attitudes of Pahari Speakers towards Punjabi language: A Sociolinguistic Study of District Bhimber - Shahbaz, Muhammad; Azam, Lubna Aram; Rahim, Ambreen (Advances in Social Sciences Research Journal, 2015)
In this study, language attitudes of the Pahari speakers towards Punjabi language in district Bhimber were investigated. District Bhimber is a city of multidimensional civilizations. Here two groups of people namely Pahari people and Punjabi people are inhabitants. Pahari people have been living among Punjabi people for more than 65 years now, but they still hold a distinct identity. However, this identity appears to be in danger because of the changing socio-linguistic scenario of the area. Questionnaires were the research methods employed to collect the data. The sample comprised of Six families of Pahari people from Bhimber city. Descriptive as well as inferential analyses were carried out to measure the attitudes of the population of this study. The language attitudes were examined through four domains: family, friendship, transaction and religion. The results from the analysis demonstrate that Pahari people have positive attitudes towards Punjabi language and a process of language shift is taking place in the Bhimber city.